We invite you to cooperation - Dorosh, Y. (Land Management, Cadastre and Land Monitoring, 2017)
Active participation in scientific publications on the pages of the magazine promotesfundamental and applied research in economics, strengthenednion of the influence of the economy on the solution of legal, political, social, ecological- and other problems of the development of society, the entry of Ukraine into international ones economic unions.